2013
DOI: 10.1111/ajt.12428
|View full text |Cite
|
Sign up to set email alerts
|

Donor Age and Early Graft Failure After Lung Transplantation: A Cohort Study

Abstract: Lungs from older adult organ donors are often unused because of concerns for increased mortality. We examined associations between donor age and transplant outcomes among 8,860 adult lung transplant recipients using Organ Procurement and Transplantation Network and Lung Transplant Outcomes Group data. We used stratified Cox proportional hazard models and generalized linear mixed models to examine associations between donor age and both 1-year graft failure and primary graft dysfunction. The rate of 1-year graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 42 publications
(58 reference statements)
1
46
0
Order By: Relevance
“…In contrast, Baldwin and colleagues [13] reported that adult LTx recipients receiving lungs from donors <18 years of age experienced higher 1-year graft failure rates. The current study could not confirm the findings of either of these two previous studies, with survival in adult LTx recipients not being improved or worsened by receiving lungs from donors younger than 18 years of age.…”
Section: Commentmentioning
confidence: 89%
See 3 more Smart Citations
“…In contrast, Baldwin and colleagues [13] reported that adult LTx recipients receiving lungs from donors <18 years of age experienced higher 1-year graft failure rates. The current study could not confirm the findings of either of these two previous studies, with survival in adult LTx recipients not being improved or worsened by receiving lungs from donors younger than 18 years of age.…”
Section: Commentmentioning
confidence: 89%
“…In adult LTx, donor age is a recognized factor regarding potential effects on clinical outcomes [13][14][15][16][17][18][19]. The majority of the current medical literature has primarily addressed the influences of older donor lungs, but few studies have assessed the impact of younger donor organs.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnitude of the association between graft failure and donor age 50 to 64 years was small; however, this effect was of most notable impact when differing recipient characteristics were considered, such as higher lung allocation score (LAS) or need for mechanical ventilation bridge to transplant. In contrast, recipients of lungs from donors aged 65 years or older had a more than twofold increased rate of 1-year graft failure (hazard ratio, 2.15; 95% CI, 1.47-3.15) when accounting for relevant recipient, donor, and procedure characteristics (13).…”
Section: Donor Usementioning
confidence: 95%